The impact of epidemic experiences on biosecurity behavior of pig farmers: an analysis based on protection motivation theory - Zhang, Wenying; Lu, Qian (One health, 2024)
Farm biosecurity is considered an important component of “One Health”. Biosecurity measures are crucial for preventing and controlling outbreaks and spread of diseases on farms. Protection motivation theory (PMT) links perception of risk and coping ability with taking preventive actions. Based on field survey data of pig farmers, this study utilizes OLS and mediating effect model to explore the impact and mechanism of epidemic experiences on farmers' implementation of biosecurity measures. The research findings are as follows: first, epidemic experiences significantly promote farmers' implementation of biosecurity measures. The conclusion remains robust after addressing potential endogeneity issues. Second, epidemic experiences, through accumulated experience, further encourage farmers to implement biosecurity measures. Third, the impact of epidemic experiences on farmers' biosecurity behavior shows heterogeneity in farm size. Compared to small-scale farmers, epidemic experiences have a greater promoting effect on biosecurity behavior of professional farmers. Therefore, emphasizing farmers' epidemic experiences, enhancing biosecurity training, and increasing farmers' awareness are of significant importance in promoting farmers' implementation of biosecurity measures.